Environmental and genetic variation of the effective radiative properties of the coat of Holstein cows under tropical conditions - Maia, Alex Sandro Campos [UNESP]; Silva, Roberto Gomes da [UNESP]; Bertipaglia, Elaine Cristina Abaker [UNESP] (Elsevier B.V., 2005)
Morphological characteristics, coat effective radiative properties, and the percentage of white colour were measured in the coats of 973 Holstein cows, and estimates of the genetic parameters were obtained for these traits, except morphological characteristics. The results showed that white coats are more dense with long, thin hairs, while the black coats are less dense with short, thick hairs. Effective transmissivity is greater in the less-dense coats with short, thin hairs, independently of coat colour. Effective reflectivity depends more on the variation in the radiative properties of the coat and skin surface rather than on the morphological characteristics of the coat. Effective absorptivity is greater in black and dense coats with long, thick hairs, than in the white and less-dense coat with short, thin hairs. All heritability estimates were of low magnitude, except for the percentage of white coat colour.
Keywords: Effective radiative properties; Hair coat; Genetic variation; Holstein cows